2018
DOI: 10.1177/1687814018758223
|View full text |Cite
|
Sign up to set email alerts
|

Development of continuously variable transmission and multi-speed dual-clutch transmission for pure electric vehicle

Abstract: Pure electric vehicles, as a promising alternative to conventional fossil fuel-powered passenger vehicles, provide outstanding overall energy-utilizing efficiency by omitting the internal combustion engine. However, because of lower energy density in battery energy storage, the driving range per charge is limited by this electrochemical power source, leading to a socalled range phobia and presenting a major barrier for large-scale commercialization. The widely adopted single-reduction gear in pure electric veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 35 publications
0
37
0
1
Order By: Relevance
“…Gear Ratios Shift Scheduling Parameters Limitations of Shift Scheduling Strategy 4-Speed [10] 14.4/10.4/7.2/5.2 Throttle Position Vehicle speed Suitable for flat road and may not be suitable for all driving cycles simultaneously. It is ensured that a certain velocity will be achieved at maximum road gradient.…”
Section: Ev Transmission Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Gear Ratios Shift Scheduling Parameters Limitations of Shift Scheduling Strategy 4-Speed [10] 14.4/10.4/7.2/5.2 Throttle Position Vehicle speed Suitable for flat road and may not be suitable for all driving cycles simultaneously. It is ensured that a certain velocity will be achieved at maximum road gradient.…”
Section: Ev Transmission Modelmentioning
confidence: 99%
“…According to this method, the gearshift schedule line is drawn by connecting the intersection points between the electric motor efficiency lines for two consecutive gears at several sets of throttle position and vehicle speed. Although the developed gearshift schedule has been applied in other studies conducted by Ruan et al [10] and Ruan et al [11], this technique is inherently complex. Moreover, although the motor efficiency and different vehicle driving conditions are considered, in practice, the traditional rule-based (i.e., throttle position and vehicle speed) gearshift schedule is a fixed gearshift schedule and may be effective for certain driving scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…various multi-speed transmissions implementations in BEV, like Automatic Transmission (AT), Automated Manual Transmission (AMT) and Continuously Variable Transmission (CVT), can be found in [8]- [10]. Results from above studies clearly demonstrated that multi-speed transmission not only improve the dynamic and economic performance of BEVs, also ease the high upfront cost by a cheaper daily cost and maintenance fee from the viewpoint of long-term ownership.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, splitting one propelling motor to two increase the possibility of higher motor operational efficiency via optimized design of motor torque-speed characteristic and engaged gear ratios. The reason of adopting a twospeed powertrain, rather than others, is that it can achieve the best balance of motor efficiency improvement and additional cost [10]. Through the proposed powertrain and related control strategy, the scientific contribution of this paper will fill the knowledge gap of existing research in following aspects:…”
Section: Introductionmentioning
confidence: 99%
“…5 The speed control of an electromagnetic direct drive vehicle robot driver has been done with neural network to obtain driving vehicle with manual transmission and automatic transmission in various test conditions. 6 The performance improvements of pure electric vehicle have been presented by utilization of multi-speed dual-clutch transmissions and continuously variable transmissions. 7 Optimization of lane-change time to avoid collisions with other vehicles has been proposed, 8 for shortest time free lane change and emergency obstacle avoidance lane change.…”
Section: Introductionmentioning
confidence: 99%